Criminal Liability of Perpetrators of Fake Marriage (Marriage Fraud) as a Form of Human Trafficking Crime - Meni Apriani; Faisal Santiago (PT. ALHAFI BERKAH INDONESIA, 2025)
The phenomenon of marriage fraud is increasingly widespread and has become one of the new schemes in human trafficking practices, particularly targeting women under the pretext of matchmaking or cross-border marriage. This modus operandi not only violates social and moral norms but also threatens human rights and involves elements of exploitation, which are essential components of human trafficking crimes as regulated in the United Nations Palermo Protocol and Law No. 21 of 2007 on the Eradication of the Crime of Human Trafficking. This study aims to analyze juridically and normatively how criminal liability can be imposed on perpetrators of marriage fraud, whether as the main offenders, recruiters, or parties facilitating this practice. By examining the provisions of the Criminal Code (KUHP), the Human Trafficking Law (UU TPPO), and other related regulations, it is found that the practice of marriage fraud can fulfill the elements of recruitment, transfer, harboring, and exploitation, which legitimately qualify as human trafficking crimes. In the context of criminal law, the liability of perpetrators includes not only individuals but also legal entities or agencies involved in organizing fake marriages. This study encourages the need for a progressive interpretation of the definition of exploitation in the Human Trafficking Law as well as strengthening protection mechanisms and education for vulnerable groups, especially women and migrant workers. With an appropriate legal approach, the practice of marriage fraud can be suppressed, and perpetrators can be held criminally accountable fairly and effectively.